Karakteristik Tanah Longsor dan Perilaku Adaptasi Masyarakat Terhadap Ketahanan Wilayah di Desa Waimatan Kecamatan Ile Ape Timur - Yasinta Tuto Tukan; Sunimbar; Ahmad hamado (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2026)
Landslide Characteristics and Community Adaptation Behavior Towards Regional Resilience in Waimatan Village, Ile Ape Timur District Landslides and community adaptation behavior in relation to regional resilience represent critical challenges in rural areas, including Waimatan Village, East Ile Ape District, Lembata Regency, Indonesia. This study aims to provide a comprehensive understanding of the geophysical and social factors influencing vulnerability levels and community adaptive capacity to landslide hazards. Specifically, the study focuses on: (1) identifying landslide characteristics that affect regional resilience in Waimatan Village, and (2) analyzing community adaptation behaviors in responding to landslide disasters. A qualitative approach with a case study design was employed. Data were collected through field observations, in-depth interviews with village authorities, community members, and the Regional Disaster Management Agency (BPBD), and photo documentation. The findings reveal that landslides in Waimatan Village are predominantly classified as debris flows and translational slides, occurring on slopes of 35°–45° with sandy clay soils that are highly susceptible to water saturation, primarily triggered by intense rainfall exceeding 150 mm/day. The study concludes that regional resilience can be strengthened through disaster-based spatial planning supported by landslide susceptibility maps, the construction of retaining structures and terracing, reforestation initiatives, and continuous community preparedness and capacity-building programs.